An Effect Virgin Coconut Oil Oral And Topical On Volume Decrease Of Foot Edema Of Male Wistar Flows Induced By –Caragenan - Dzil Fikri; Ermi Girsang; Ali Napiah Nasution; Linda Chiuman (International Journal of Health and Pharmaceutical (IJHP), 2022)
Virgin Coconut Oil(VCO) is virgin coconut oil that is made enzymatically. The content of saturated fatty acids and flavonoid compounds in VCO can be used as an anti-inflammatory drug. This study aims to determine the activity of VCO as an anti-inflammatory. Anti-inflammatory activity was tested using the method of calculating the percentage of inflammation inhibition in white rat paws induced by intraplantar 1% carrageenan solution. The decrease in edema in the rat's feet was measured using a plethysmometer for 360 minutes. The results showed that VCO at a dose of 0.4 ml/200 g BW and 0.8 ml/200 g BW gave anti-inflammatory activity with the percentage of inflammation inhibition of 64.34 ± 9.90 and 52.66 ± 8, respectively. 94. The anti-inflammatory activity of VCO at a dose of 0.4 ml/ 200 g BW and a dose of 0.